Mg-Ca0.3 Electrochemical Activity Exposed to Hank’s Physiological Solution and Properties of Ag-Nano-Particles Deposits - González Murguía, José Luis; Veleva, Lucien; Rodríguez Gattorno, Geonel; Figueroa Torres, Mayra Zyzlila; Feliu, Sebastián (Molecular Diversity Preservation International, 2021)
This work compares the degradation of Mg and Mg-Ca0.3 alloy when they are exposed for 14 days to Hank’s solution at 37 °C. A combination of immersion test, electrochemical techniques (PDP, EIS, EN), and surface characterization methods (SEM-EDS, XRD, and XPS) were carried out. The pH change over time, the lower mass loss (≈20%), and the lower concentration of the released Mg2+ ions (≈3.6 times), as well as the lower level of the surface degradation, allowed to consider the positive effect of Ca, presenting Mg-Ca0.3 alloy with lower electrochemical activity than that of Mg. The positive effect of Ca may be due to the formed layer characteristics on the alloy surface, which impedes the cathodic hydrogen evolution and Mg-ions release. The electroless deposited Ag-nano-particles (Ag-NPs) on Mg-Ca0.3 surface were characterized by SEM-EDS, XRD, UV-Vis, and contact angle. The agar-diffusion test was used to compare the growth of Staphylococcus aureus and Escherichia coli bacteria on Mg-Ca0.3 in the presence of Ag-NPs deposits in different size. Zeta-potential of the bacteria was negative, with respect to pH of the Mueller-Hinton culture broth. The greater antibacterial effect of S. aureus was attributed to its more negative zeta-potential, attracting more released Ag+ ions.